Non casas, sed etiam domos fundatas: the origins of architecture from Vitruvius - Manenti, Leandro (Revista Archai, 2023)
This work discusses the origin of the architect and the architecture presented in the treatise De Architectura by Vitruvius and its association with imitation. It is discussed the Vitruvian notion of the progression of humanity and its connections with the architect and the establishment of Architecture as the science of the architect. The proposal of training for professionals from various areas is analyzed, which would guarantee, according to Vitruvius, a generalist training and at the same time specialized in their field. It also discusses the attributes necessary, according to the author, for a good professional, which would allow him to achieve recognition for his authority.